Effects of Attrition Shoes on Kinematics and Kinetics of Lower Limb Joints During Walking - Chen, Shane Fei; Wang, Yan; Peng, Yinghu; Zhang, Ming (Frontiers in Bioengineering and Biotechnology, 2022)
Shoe attrition is inevitable as wearing time increases, which may produce diverse influences on kinematics and kinetics of lower limb joints. Excessive attrition may change the support alignment and lead to deleterious impacts on the joints. The study identifies the biomechanical influences of aging shoes on lower limb joints. The shoes in the experiment were manually worn in the lateral heel. Nineteen healthy participants including thirteen males and six females were recruited to conduct walking experiments wearing attrition shoes (AS) and new shoes (NS) with a random order. A Vicon Motion Analysis system was used to collect kinematic data and ground reaction force, respectively. Kinematic and kinetic parameters of the hip, knee, and ankle joints were calculated using the Anybody musculoskeletal model and compared between the two conditions AS and NS. The results showed that wearing an attrition shoe decreased the plantarflexion angle and plantarflexion moment of the ankle joint, while significantly increasing the magnitude of the first peak of knee adduction moment and hip abduction moment and hip internal rotation moment (p<0.05). The results of the study implied that wearing attrition shoes is not recommended for those people with knee problems, due to the increase in medial loading.